PERLINDUNGAN HAK PENDIDIKAN ANAK TERLANTAR MENURUT UNDANG UNDANG PERLINDUNGAN ANAK - Rofilah Khasanatun Daroini (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The right to education is a fundamental right of every child that must be guaranteed by the state, including neglected children as a vulnerable group. In practice, however, the fulfillment of the educational rights of neglected children still faces various challenges, requiring a comprehensive legal analysis. This study aims to examine the legal framework governing the protection of neglected children’s right to education and to analyze the obligations and responsibilities of the state in ensuring the fulfillment of this right based on Law Number 35 of 2014 on Child Protection. This research employs a normative juridical method using statutory and conceptual approaches, conducted through the analysis of relevant laws and legal literature. The results show that the Child Protection Law provides a strong normative foundation for the protection of neglected children’s right to education, particularly through provisions that impose obligations on the state to respect, protect, and fulfill children’s rights. Through the perspective of the welfare state theory, this study highlights that the fulfillment of neglected children’s educational rights constitutes a legal obligation of the state as the guarantor of social welfare. Therefore, the protection of neglected children’s right to education must be understood as an imperative state responsibility oriented toward the best interests of the child.